Pendampingan Pelaku Bidang Usaha Mikro, Kecil dan Menengah (UMKM) dalam Upaya Pengembangan Potensi Lokal Produk-Produk Pesisir di Kelurahan Ngemplakrejo Kota Pasuruan - Nuruddin, Nuruddin; Fauzi, M. Asif Nur; Zakkiyah, Azri; Machrus, Ali (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This community service program aims to assist Micro, Small, and Medium Enterprises (MSMEs) in Ngemplakrejo Village, Pasuruan City in developing the local potential of coastal products. Ngemplakrejo Village has a wealth of coastal natural resources that have high potential to be processed into products with economic value, but many MSMEs in this area face obstacles in optimizing this potential. These obstacles include lack of knowledge about product processing and packaging, minimal market access, and the absence of an effective branding strategy. This assistance is carried out through several stages, namely identification of local product potential, technical training in product processing and packaging, and development of branding and marketing strategies. In addition, this program also provides education on business legality to increase consumer confidence and expand market reach. With this assistance, it is hoped that MSMEs in Ngemplakrejo Village will be able to improve product quality, strengthen competitiveness, and optimize existing local economic potential. The results of this program are expected to have a positive impact on MSME actors, both in increasing business capacity and in expanding the market for coastal products, so that the contribution of MSMEs to the local economy is increasingly significant.